Impact of jujube fruit on serum lipid profile, glycemic index, and liver function: a systematic review and meta-analysis - Mostafa Ahmadi; Hoda Shirafkan; Seyyed Ali Mozaffarpur; Maedeh Rezghi (Nutrition & Diabetes)
Abstract Jujube is a widely consumed fruit with a long history in traditional medicine. Numerous studies have explored its potential effects on various health parameters. However, the overall quality of this evidence and the specific impact of jujube on metabolic syndrome remain unclear. This meta-analysis investigates the effect of jujube on body mass index, serum lipid profile, blood sugar levels, and other metabolic factors and blood indicators. The databases Web of Science, Scopus, PubMed, Google Scholar, and SID were searched up to September 2023. Our review included various clinical studies written in English and Persian that focused on the effect of jujube on lipid profiles. In vivo, in vitro, review studies, book chapters, observational studies, and low-quality studies based on critical appraisal tools were excluded from the analysis. A total of seven studies involving 483 participants were included in this review. Jujube significantly reduced BMI and TG, and also markedly decreased FBS in subjects with type 2 diabetes. Furthermore, the results varied significantly based on subgroups defined by dosage, treatment duration, and disease type. Notably, LDL and total cholesterol levels showed a significant decrease within some of these subgroups. However, HDL, AST, and ALT did not have significant changes. The findings suggest that jujube may exert beneficial effects on metabolic diseases, particularly in patients with hyperlipidemia and type 2 diabetes. However, the overall quality of the evidence is limited, and further research is needed to confirm these findings and elucidate the mechanisms underlying jujube’s effects. Impact of jujube fruit on serum lipid profile, glycemic index, and liver function: a systematic review and meta-analysis.